Tolerogenic dendritic cells generated in vitro using a novel protocol mimicking mucosal tolerance mechanisms represent a potential therapeutic cell platform for induction of immune tolerance - Dao Nyesiga, Gillian; Pool, Lieneke; Englezou, Pavlos C.; Hylander, Terese; Ohlsson, Lars; Appelgren, Daniel; Sundstedt, Anette; Tillerkvist, Kristina; Romedahl, Hanne R.; Wigren, Maria (Frontiers in Immunology, 2023)
Dendritic cells (DCs) are mediators between innate and adaptive immunity and vital in initiating and modulating antigen-specific immune responses. The most important site for induction of tolerance is the gut mucosa, where TGF-, retinoic acid, and aryl hydrocarbon receptors collaborate in DCs to induce a tolerogenic phenotype. To mimic this, a novel combination of compounds – the synthetic aryl hydrocarbon receptor (AhR) agonist IGN-512 together with TGF-β and retinoic acid – was developed to create a platform technology for induction of tolerogenic DCs intended for treatment of several conditions caused by unwanted immune activation. These in vitro-generated cells, designated ItolDCs, are phenotypically characterized by their low expression of co-stimulatory and activating molecules along with high expression of tolerance-associated markers such as ILT3, CD103, and LAP, and a weak pro-inflammatory cytokine profile. When co-cultured with T cells and/or B cells, ItolDC-cultures contain higher frequencies of CD25+Foxp3+ regulatory T cells (Tregs), CD49b+LAG3+ type 1 regulatory T (Tr1), and IL-10-producing B cells and are less T cell stimulatory compared to cultures with matured DCs. Factor VIII (FVIII) and tetanus toxoid (TT) were used as model antigens to study ItolDC antigen-loading. ItolDCs can take up FVIII, process, and present FVIII peptides on HLA-DR. By loading both ItolDCs and mDCs with TT, antigen-specific T cell proliferation was observed. Cryo-preserved ItolDCs showed a stable tolerogenic phenotype that was maintained after stimulation with LPS, CD40L, or a pro-inflammatory cocktail. Moreover, exposure to other immune cells did not negatively impact ItolDCs’ expression of tolerogenic markers. In summary, a novel protocol was developed supporting the generation of a stable population of human DCs in vitro that exhibited a tolerogenic phenotype with an ability to increase proportions of induced regulatory T and B cells in mixed cultures.